Microlia cayaponia, a new pollen-feeder species from Brazil (Staphylinidae: Aleocharinae: Hoplandriini) and its potential competitionin pollinator activity in Cayaponia plants (Cucurbitaceae) - Zilberman, Bruno; Cardoso, Renan Kobal De Oliveira Alves; Pires-Silva, Carlos M.; Santos, Isabel Alves Dos (Zootaxa, 2023)
Microlia Casey is a genus of small rove beetles from the New World and Australasia. Many species are recorded to be associated with the flowers of Cucurbitaceae, Solanaceae, Asteraceae, and Monimiaceae. In this work, a new species from Brazil associated with flowers of Cayaponia (Cucurbitaceae), Microlia cayaponia Zilberman & Pires-Silva sp. nov., is described and illustrated. Aspects of its natural history are also investigated, with insights on foraging, reproduction, and the supposed impact on the plant and pollinator’s fitness.